Optical-microphysical Properties of Saharan Dust Aerosols and Composition Relationship Using a Multi-wavelength Raman Lidar, in Situ Sensors and Modelling: a Case Study Analysis - Papayannis, Alexandros D.; Amiridis, Vassilis; Mamouri, Rodanthi-Elisavet (My University, 2012)
A strong Saharan dust event that occurred over the city of Athens, Greece (37.9° N, 23.6° E) between 27 March and 3 April 2009 was followed by a synergy of three instruments: a 6-wavelength Raman lidar, a CIMEL sun-sky radiometer and the MODIS sensor. The BSC-DREAM model was used to forecast the dust event and to simulate the vertical profiles of the aerosol concentration. Due to mixture of dust particles with low clouds during most of the reported period, the dust event could be followed by the lidar only during the cloud-free day of 2 April 2009. The lidar data obtained were used to retrieve the vertical profile of the optical (extinction and backscatter coefficients) properties of aerosols in the troposphere. The aerosol optical depth (AOD) values derived from the CIMEL ranged from 0.33-0.91 (355 nm) to 0.18-0.60 (532 nm), while the lidar ratio (LR) values retrieved from the Raman lidar ranged within 75-100 sr (355 nm) and 45-75 sr (532 nm). Inside a selected dust layer region, between 1.8 and 3.5 km height, mean LR values were 83 ± 7 and 54 ± 7 sr, at 355 and 532 nm, respectively, while the Ångström-backscatter-related (ABR 355/532) and Ångström-extinction-related (AER 355/532) were found larger than 1 (1.17 ± 0.08 and 1.11 ± 0.02, respectively), indicating mixing of dust with other particles. Additionally, a retrieval technique representing dust as a mixture of spheres and spheroids was used to derive the mean aerosol microphysical properties (mean and effective radius, number, surface and volume density, and mean refractive index) inside the selected atmospheric layers. Thus, the mean value of the retrieved refractive index was found to be 1.49( ± 0.10) + 0.007( ± 0.007)i, and that of the effective radiuses was 0.30 ± 0.18 μm. The final data set of the aerosol optical and microphysical properties along with the water vapor profiles obtained by Raman lidar were incorporated into the ISORROPIA II model to provide a possible aerosol composition consistent with the retrieved refractive index values. Thus, the inferred chemical properties showed 12-40% of dust content, sulfate composition of 16-60%, and organic carbon content of 15-64%, indicating a possible mixing of dust with haze and smoke. PM10 concentrations levels, PM10 composition results and SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-ray) analysis results on sizes and mineralogy of particles from samples during the Saharan dust transport event were used to evaluate the retrieval.
Keywords: Aerosols; Mineralogy; Dust; Radiometers; Open access publishing